2011
DOI: 10.1002/tox.20532
|View full text |Cite
|
Sign up to set email alerts
|

Involment of p53, Bax, and Bcl‐2 pathway in microcystins‐induced apoptosis in rat testis

Abstract: It has been reported that microcystins (MCs) could accumulate in the gonads of mammals and MCs exposure exerts obvious toxic effects on male reproductive system of mammals. We have comfirmed that MCs could accumulate and induce apoptosis in rat testis. The p53, Bax, and Bcl-2 protein play important roles in mitochondria-dependent apoptotic pathway, and this study aimed to investigate whether the p53, Bax, and Bcl-2 pathway is involved in microcystins-induced apoptosis in rat testis and discussed the possible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Because Sertoli cells are the main cells expressing FasL in seminiferous tubules and Fas is localized to specific germ cell subtypes, the authors believed that MCs can cause damage directly to Sertoli cells. Li et al [58] also confirmed that MCs could induce apoptosis in testis of Wistar rats that received i.v. injection of CCEs, and p53, Bax, and Bcl-2 might contribute to the mitochondria-dependent apoptotic pathway.…”
Section: Reproductive Toxicity Of Mcs On Mammalsmentioning
confidence: 85%
See 2 more Smart Citations
“…Because Sertoli cells are the main cells expressing FasL in seminiferous tubules and Fas is localized to specific germ cell subtypes, the authors believed that MCs can cause damage directly to Sertoli cells. Li et al [58] also confirmed that MCs could induce apoptosis in testis of Wistar rats that received i.v. injection of CCEs, and p53, Bax, and Bcl-2 might contribute to the mitochondria-dependent apoptotic pathway.…”
Section: Reproductive Toxicity Of Mcs On Mammalsmentioning
confidence: 85%
“…The competition between Bax and Bcl-2 determines the cell fate in terms of execution of apoptosis or survival. However, MCs induced expression of p53 and the ratio of Bax to Bcl-2 [58], led to the opening of MPT pores, mitochondrial swelling (a common feature of mitochondrial membrane permeabilization) [33], loss of inner mitochondrial membrane potential (MMP), and mitochondrial release of cyt c [123]. Once cyt c is released from the intermembrane space of mitochondria to the cytoplasm, the cell is committed to die by activation of the apoptotic caspase cascade and nucleic DNA fragmentation, or necrosis due to collapse of the respiratory function [72].…”
Section: Apoptosis/necrosismentioning
confidence: 92%
See 1 more Smart Citation
“…As a tumor suppressor gene, the expression of P53 has been reported to be upregulated in rat testis exposed to microcystins, which showed that the P53 pathway is involved in microcystin-induced apoptosis [Li et al 2011]. Variants of codon 72 of the TP53 gene were described to be associated with the differential expression of the gene in cultured cells [Shi et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA isolation, synthesis of first-strand cDNA, and real-time PCR were performed followed the method described previously (Li et al, 2011). Briefly, HEK293 cells were cultured with 0 or 10 M MC-LR, and the cells were harvested 10 h after treatment.…”
Section: Cdna Preparation and Real-time Pcrmentioning
confidence: 99%